Optimization of the fan coil cooling system and the air source heat pump using a moderated mediation model - ONAT, AYHAN (My University, 2024)
The data obtained from a heating and cooling system comprised of a fan coil unit integrated air source heat pump used in Istanbul, Turkey, as well as data on outdoor conditions, was analyzed in this study. The analysis was carried out with the help of the moderated mediation model, which is included as a process analysis in the \"Statistical Package for the Social Sciences\" application. In this study, a mathematical model of the moderated mediation model was created and the efficiency coefficients of the parameters effecting performance were calculated. It was discovered that the effect of medium and high relative humidity values on the outdoor temperature was about 4.81%. The heat pump fails to transmit heat to the environment outside as a result of medium and high relative humidity values increasing the outdoor temperature. As a result of this it has been found that relative humidity values have a negative effect on the water temperature entering the fan coil unit by approximately -1.18%. This result of the study shows that the outlet water temperature of the fan coil unit does not adequately cool the rooms in the summer. It has been discovered that while wind velocity negatively affects performance affecting parameters, low relative humidity values have no effect on them.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENERGY & FUELS; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Renewable Energy, Sustainability and the Environment; Physical Sciences; air source heat pump; fan coil; moderated mediation model; outdoor temperature; relative humidity